Respuesta :
Answer:
[tex]\frac{d}{dx}(-xcos3x)= 3x \ sin(3x)- cos(3x)[/tex]
Step-by-step explanation:
Use the Product Rule for derivatives, which states that:
- [tex]\frac{d}{dx} =[f(x)g(x)]= f(x)g'(x)+f'(x)g(x)[/tex]
In the function we are given, [tex]f(x)=-x \cos3x[/tex], we can break it up into two factors: -x is being multiplied by cos3x.
Now, we have the factors:
- [tex]-x \\ $cos 3x[/tex]
Before using the product rule, let's find the derivative of cos3x using the chain rule and the power rule.
- [tex]\frac{d}{dx}(cos3x)= \frac{d}{dx} (cos3x) \times \frac{d}{dx} (3x) \\ \frac{d}{dx}(cos3x)= (-sin3x) \times 3 \\ \frac{d}{dx} (cos3x) = -3sin(3x)[/tex]
Now let's apply the product rule to f(x) = -xcos3x.
- [tex]\frac{d}{dx}(-xcos3x)= (-x)(-3sin3x) + (-1)(cos3x)[/tex]
Simplify this equation.
- [tex]\frac{d}{dx}(-xcos3x)= (x)(3sin3x) - (cos3x)[/tex]
Multiply x and 3 together and remove the parentheses.
- [tex]\frac{d}{dx}(-xcos3x)= 3x \ sin(3x)- cos(3x)[/tex]
Therefore, this is the derivative of the function [tex]f(x)=-xcos3x[/tex].
Hi there!
[tex]\large\boxed{f'(x) = -cos3x + 3xsin3x}[/tex]
[tex]f(x) = -xcox3x\\\\\text{Use the product rule and chain rule to solve for the derivative:}\\\\\frac{dy}{dx}= -cos3x + (-x * (-sin3x) * 3)\\\\= -cos3x + 3xsin3x[/tex]